AIRCRAFT POWER SUPPLY SYSTEM DESIGN PROCESS AS AN AUTOMATION OBJECT - B. V. Zhmurov (Научный вестник МГТУ ГА, 2018)
The process of designing aviation electrical power systems (EPS) is related to the need to fulfill a number of requirements of normative and technical documents and to conduct a large number of calculations. Experience has shown that it is not possible to obtain reliable initial data on the nature and magnitude of electricity consumption by electricity receivers (end users) at the early stages of design. The composition of the electric power receivers and the power consumption of electricity during the design process are repeatedly changed. This leads to the need to repeatedly perform tasks related to the synthesis of primary and secondary systems of generation and calculation.The desire to improve the efficiency of EPS led to the emergence of new standardized types of electrical energy - 270 V DC and 380 V three-phase AC of stable and unstable frequency. It follows that it is possible to implement a rather large number of options for EPS structures, and there may be several secondary EPS or, in general, EPS of a third or higher level.The lack of ready-made aviation energy converters implies the impossibility of using ready-made components, and the development of specific devices should be coordinated with the development of EPS. In this case, one of the results of EPS design will be a set of requirements for the devices and units of the EPS projected.In any case, the design process for EPS aircraft requires a lot of iterations that take into account the change in both the raw data and the constraints on the EPS elements and the design process itself.The traditional approach to the design of EPS aircraft, assuming the knowledge of the designer of dozens of GOSTs (State All-Union standards) and OSTs (All-Union standarts) regulating the design stages of EPS, as well as the existence of standard EPS structures, from which a specific choice is made, is practically impossible at present. The only way to consciously approach the problem of designing EPS aircraft and take into account all the requirements of the customer and the regulatory and technical documentation is its automation.Automation of the design of EPS aircraft as an optimization task involves the formalization of the object of optimization, as well as the choice of the criterion of efficiency and control actions. Under the object of optimization in this case we mean the design process of the EPS, the formalization of which includes formalization and the design object – the aircraft power supply system.